2005
DOI: 10.3346/jkms.2005.20.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Subsets and Mood States in Panic Disorder Patients

Abstract: This study was conducted to examine lymphocyte subset counts and mood states in panic disorder patients. Twenty patients with panic disorder and 20 age- and gender-matched normal healthy subjects were recruited for the study. We used the Spielberger State (STAIS) & Trait (STAIT) Anxiety Inventory, Hamilton Depression Rating scale (HAMD) and Hamilton Anxiety Rating scale (HAMA) to measure mood states in all subjects. Lymphocyte subsets counts were made by flow cytometry. Panic patients showed significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
(30 reference statements)
0
14
0
3
Order By: Relevance
“…Several studies have found no significant differences in cytokine levels between panic disorder patients and healthy subjects [10][11][12][13], as consistent with our results, except those related with the levels of IL-12 and IFN-γ. Park et al [24] found that panic disorder patients exhibited no differences with respect to the numbers of immune cells, except for a reduced proportion of T suppressor cells and an increased T helper cell/T suppressor cell ratio, as compared with normal healthy subjects. Reduced levels of IL-2 in panic disorder patients have also been reported [14].…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have found no significant differences in cytokine levels between panic disorder patients and healthy subjects [10][11][12][13], as consistent with our results, except those related with the levels of IL-12 and IFN-γ. Park et al [24] found that panic disorder patients exhibited no differences with respect to the numbers of immune cells, except for a reduced proportion of T suppressor cells and an increased T helper cell/T suppressor cell ratio, as compared with normal healthy subjects. Reduced levels of IL-2 in panic disorder patients have also been reported [14].…”
Section: Discussionmentioning
confidence: 97%
“…) and alterations of other immune cell markers (Rapaport ; Park et al. ) in PD, with data showing heterogeneous results. No significant changes in any of these variables could be found during CO 2 inhalation‐induced panic (van Duinen et al.…”
Section: Laboratory/biological Studiesmentioning
confidence: 99%
“…However, other studies have shown that there was no difference in T-lymphocyte subsets between panic disorder patients and control groups 14,15). There should be more consideration for these results, and the precise molecular mechanisms of antiviral immunologic pathways should be studied further.…”
Section: Discussionmentioning
confidence: 87%